Flipping the classroom to promote higher order thinking skill: A case of Chinese undergraduate students - Ariani Selviana Pardosi; Liu Yue Ming (Journal of Educational Management and Instruction (JEMIN), 2021)
Flipped learning approach has recently gained much more attention and has widely been utilized as a new approach to assist student-centered learning activities across different contexts of teaching. The present study aims to examine the effect of flipped learning instruction on undergraduate students’ development of higher order thinking skills (HOTS). Drawing on a quasi-experimental design, this study recruited 70 Chinese science education students enrolled in ‘teaching with technology’ course; they were equally divided into flipped (experiment) and non-flipped (control) groups. Data were obtained from pre-tests and post-tests in both groups using a higher order thinking skill test, and were analyzed by means of sample t-test using IBM-SPSS version 24. The results showed that flipped group students outperformed the non-flipped students in terms of HOTS performance. There was a significant different between the results of flipped group students’ pre-test and post-test scores (p-value: 0.000 < 0.05). It suggests that the flipped learning instruction has a significant effect on the Chinese undergraduate students’ HOTS development. This study contributes to providing valuable insights for instructors and college curricula designers to incorporate flipped learning approach in teaching at university level.